Long term risk of recurrence of ptosis repair: implications for surgical counseling and follow-up - Cohen, Dana; Passaro, Maria Laura; Grachova, Elena; Riccardo, Alessia; Iuliano, Adriana; Lanni, Vittoria; Matarazzo, Francesco; D’Aponte, Antonella; Costagliola, Ciro; Strianese, Diego (Frontiers in Ophthalmology, 2026)
PurposeTo evaluate recurrence rates after surgical correction of ptosis in adults, with emphasis on differences between aponeurotic and non-aponeurotic etiologies, and to identify predictors of recurrence.MethodsThis retrospective, single-center cohort study included a series of patients undergoing ptosis surgery at single tertiary referral Oculoplastic Unit at University of Naples Federico II (2014–2024). Data collected included demographics, ptosis subtype, surgical technique, preoperative marginal reflex distance (MRD), levator function, systemic comorbidities, and latency to treatment. The primary outcome was recurrence of ptosis. Kaplan–Meier estimates and Cox proportional hazards models were used to evaluate recurrence-free survival and predictors of recurrence. Fisher’s exact test assessed associations with comorbidities.ResultsA total of 122 patients (152 eyes) were included (mean age 59.7 ± 23.8 years; 54.6% male). The median follow-up was 165.1 weeks (IQR 67.0–330.6). Aponeurotic ptosis accounted for 50.7% of eyes, congenital for 30.3%, and myogenic for 18.4%. Levator repair was the most common surgical approach (78.9%). Recurrence occurred in 35 eyes (23.0%) during a median follow-up period of 165.1 weeks (IQR 67.0–330.6), Recurrence was significantly lower in aponeurotic vs non-aponeurotic ptosis (log-rank p = 0.048). In multivariable Cox analysis, non-aponeurotic ptosis was the only independent predictor of recurrence (HR 2.44, 95% CI: 1.13–5.28; p = 0.023). MRD, levator function, latency to treatment, and systemic comorbidities were not meaningfully associated with recurrence.ConclusionsPtosis recurrence after surgery was significantly less frequent in aponeurotic ptosis group compared to other forms. Etiology, rather than preoperative assessment measurements and surgical technique, was the primary determinant of long-term outcomes. These findings highlight the importance of etiology-driven surgical counseling and follow-up planning.